Kinetic insights into ϵ‐caprolactone synthesis: Improvement of an enzymatic cascade reaction. Issue 6 (14th March 2017) - Scherkus, Christian; Schmidt, Sandy; Bornscheuer, Uwe T.; Gröger, Harald; Kara, Selin; Liese, Andreas
ABSTRACT: A computational approach for the simulation and prediction of a linear three‐step enzymatic cascade for the synthesis of ϵ‐caprolactone (ECL) coupling an alcohol dehydrogenase (ADH), a cyclohexanone monooxygenase (CHMO), and a lipase for the subsequent hydrolysis of ECL to 6‐hydroxyhexanoic acid (6‐HHA). A kinetic model was developed with an accuracy of prediction for a fed‐batch mode of 37% for substrate cyclohexanol (CHL), 90% for ECL, and >99% for the final product 6‐HHA. Due to a severe inhibition of the CHMO by CHL, a batch synthesis was shown to be less efficient than a fed‐batch approach. In the fed‐batch synthesis, full conversion of 100 mM CHL was 28% faster with an analytical yield of 98% compared to 49% in case of the batch synthesis. The lipase‐catalyzed hydrolysis of ECL to 6‐HHA circumvents the inhibition of the CHMO by ECL enabling a 24% higher product concentration of 6‐HHA compared to ECL in case of the fed‐batch synthesis without lipase. Biotechnol. Bioeng. 2017;114: 1215–1221. © 2017 Wiley Periodicals, Inc. Abstract : A kinetic model of an enzymatic cascade reaction for the synthesis of epsilon‐caprolactone and further hydrolysis was developed. Each catalytic reaction step was investigated illustrating the kinetics in detail. Hence, simulations for batch and fed‐batch syntheses could be conducted with a prediction of the experimental data. Higher product concentrations could be reached by a subsequent hydrolysis of epsilon‐caprolactone to 6‐hydroxyhexanoic acid.